2004
DOI: 10.1016/j.ics.2004.02.081
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological analysis of influenza pandemics in Shizuoka Prefecture and all Japan

Abstract: 1) Seroepidemiological analysis of influenza pandemics (1986 -2003) in Shizuoka Prefecture and all Japan revealed differences in geographical, annual, seasonal, and age distributions.(2) For 17 years, the pandemics generally began at the 50th week every year showing over 1.0 patient/clinic, reached the peak at 5th week the following year, and ended over 10 -15th week. Two big A/H3N2 pandemics were seen in 1989/1990 and 1997/1998 seasons, claiming over 1 million patients in Japan. (3) As herald strains, A/H3N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A study published by Miyamoto et al (2004), reported that pandemic disease is dependent on acquired/vaccinated immunity and weather conditions that are catastrophic to several viruses such as severe acute respiratory syndrome corona virus (Miyamoto et al, 2004). The less effect of COVID-19 on children is not because of vaccines, as there is no significant cross reactivity against SARS-CoV, which indicates that decreased symptoms of SARS-CoV in children may be attributed to other reasons (Yu et al, 2007).…”
Section: Physiological Role Of Thymus In Children Against Viral Infec...mentioning
confidence: 99%
“…A study published by Miyamoto et al (2004), reported that pandemic disease is dependent on acquired/vaccinated immunity and weather conditions that are catastrophic to several viruses such as severe acute respiratory syndrome corona virus (Miyamoto et al, 2004). The less effect of COVID-19 on children is not because of vaccines, as there is no significant cross reactivity against SARS-CoV, which indicates that decreased symptoms of SARS-CoV in children may be attributed to other reasons (Yu et al, 2007).…”
Section: Physiological Role Of Thymus In Children Against Viral Infec...mentioning
confidence: 99%
“…(1) The early detection of herald strains like B/Shizuoka/1/98 strain in interpandemic periods every year is very important for vaccine-candidated strains and those productive supply in the following seasons [1][2][3]. (2) Low anti-HA antibody (HI) titers under 10 in massive prevention suggest that the next pandemics due to new avian subtypes, e.g., H5N1 in Hong Kong, H7N7 in the Netherlands and other highly pathogenic avian influenza (HPAI) also could be predicted for a world-scale outbreak in the near future among unvaccinated population [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, virological, serological and genetic analyses were done with regard to (1) pathogen's information -mainly the viral subtypes (vaccine, herald and pandemic/ endemic strains) and (2) patient's information-mainly percentage (%) of hemagglutination inhibition (HI) antibody titers of Shizuoka Prefectural people in order to serve the prediction of usual and new (avian) types of influenza pandemics -interpandemics in the near future in all Japan. (B) The following results [1][2][3] were clarified from viral and serological analyses of influenza pandemics in Japan:…”
Section: Introductionmentioning
confidence: 99%
“…Although the immune system developed via vaccination is effective against pandemic diseases, the lack of an effective vaccine against COVID-19 so far, suggests the presence of other defense mechanisms against COVID-19 in children [ 7 ]. In this editorial, we want to discuss a theory, which has not been mentioned before.…”
mentioning
confidence: 99%